2017
DOI: 10.1016/j.omtm.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12 Promotes Stem Cell Recruitment and Uterine Repair after Injury in Asherman’s Syndrome

Abstract: Asherman’s syndrome is an acquired condition of uterine fibrosis and adhesions in response to injury that adversely affects fertility and pregnancy. We have previously demonstrated that bone marrow-derived mesenchymal stem cells (BMDSCs) contribute to uterine repair after injury and that stem cells supplementation improves fertility. Here, we demonstrate that CXCL12 is the chemokine that mediates stem cell engraftment and functional improvement using a murine model of Asherman’s syndrome. After uterine injury,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 36 publications
0
52
0
Order By: Relevance
“…The disappearance of normal endometrium structure changes the functionality of this organ . Loss of native stem cells or injury of stem cells niche caused by iatrogenic curettage often leads to failed regeneration of the functional layer of endometrium and results in amenorrhea, infertility, or pregnancy complications …”
Section: Discussionmentioning
confidence: 97%
“…The disappearance of normal endometrium structure changes the functionality of this organ . Loss of native stem cells or injury of stem cells niche caused by iatrogenic curettage often leads to failed regeneration of the functional layer of endometrium and results in amenorrhea, infertility, or pregnancy complications …”
Section: Discussionmentioning
confidence: 97%
“…Asherman's syndrome is an acquired condition of uterine fibrosis and adhesions in response to injury. 54 Specifically, following uterine injury to create a model of AS, it was demonstrated that CXCL12 augmentation increased BMDSC engraftment and that the CXCL12 receptor (CXCR4) antagonist, ADM3100 (Plerixafor which is FDA approved), blocked stem cell recruitment. 41,49-51 While the generation and growth of the uterine endometrium are important physiologically for reproduction, it is defective in AS.…”
Section: Xcl12 S I G Naling In a S Herman ' S Syndromementioning
confidence: 99%
“…49,53 Aside from surgery, which is not fully effective, no therapies are currently available to treat this disease. 54 Unlike the case for endometriosis in which the CXCL12/ CXCR4/CXCR7 axis plays a key role in promoting disease, the interaction of CXCL12 with CXCR4 on murine models of AS has shown a decrease in fibrosis and improved fertility. Sites of injury are known to increase expression of CXCL12; however, CXCL12 is rapidly proteolyzed and does not mobilize cells for a prolonged duration.…”
Section: Xcl12 S I G Naling In a S Herman ' S Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…The most common early symptoms of IUA patients are menstrual abnormalities, recurrent abdominal pain, and amenorrhea [4]. IUA often leads to infertility, recurrent miscarriage, and various complications of pregnancy, such as placenta implantation, placental abruption, preterm premature rupture of membranes, and developmental abnormalities in the fetus as a result of the loss of normal endometrium and insu cient the blood supply to the uterus [5][6][7]. In recent years, IUA has become one of the common causes of female infertility in China, and its incidence has been on the rise with uterine cavity surgery increasing [4,8].…”
Section: Introductionmentioning
confidence: 99%